Abung dit egongot crossing the gap between traditional and contemporary Ilongo architecture - Jamero, Jan Ella B. (College of Architecture, University of the Philippines Diliman, 2018)
The Ilongot Tribal Vilage is a community-initiated project in an effort to preserve the culture and tradition of the Ilongot Tribe; to present their tribe's culture and tradition, framed through their perspective. The village is consisted of a mix of traditional and hybrid traditonal-contemporary Ilongot buildings. The goal of the project is to provide the community with greater ability to translate their vision into designs. The methodology was devised with the following questions in mind: "How do we design building types that are not yet existing in the traditional Ilongot community? What is Ilongot Architecture?" Information from library research frequenting and immersing into the community were processed, to birth the inspirations and concepts used in designing the hybrid traditional-contemporary Ilongot structures. Ultimately, the questions which the project methodology seeks to answer not only in the affirmative, but with a resounding yes are "Will the design be readily integrated into the community's sensibilities? Will the build it?".